Social representations and prejudice against indigenous people in Argentina - Barreiro, Alicia (2019)
This study describes the social representation of indigenous people and analyzes the existence of differential positioning according to subtle and blatant prejudice levels. Participants (N = 304 residents from Buenos Aires, aged 18-41) answered the word association technique and the subtle and blatant prejudice scale towards indigenous people. The analysis of the word association’s rank and frequency indicated an anachronistic representation of indigenous people that places them outside culture. One-way Correspondence Factorial Analysis showed that participants with low and medium levels of subtle prejudice considered indigenous people as Argentinean and attribute their current situation to the massacre they suffered in the past. Participants with high levels of subtle prejudice devalued them and did not consider them as Argentine.